THE EARTH AS IT SHOULD: EXPLORATION OF BANANA STEM FIBER PAPER AS PRINT SURFACE FOR PRINTMAKING - Kemalahayati, Dyah
Human’s ability to manipulate their habitat becomes the important factor that enables the whole species’ spread and survival. To this day, humans are becoming more used to their role as the modifier who can always manipulate earth’s form. Technological development also becomes an important factor which supports humans in manipulating the earth. This humans’ intervention can result in either the earth’s destruction or the sustainable life of its inhabitants, depending on how humans treat their technology usage. Haphazard and careless ways will result in the earth’s destruction. The inspiration for this final project set off from the artist’s own subjective personal intuition, perhaps more specifically the nature as a human to control the environment surrounding her. A feeling that drives homo sapiens to rule and change the earth. This problem is what ushered the writer into a chain of material exploration in order to find the right material for delivering her views of that problem. The main material that the writer used are banana stems and leaves, as natural materials that are plenty in Indonesia. After experimenting on the materials as matrix and pigment, the exploration was ended with paper from banana stem fiber that the writer used as the final project artworks’ material. The paper becomes a surface which underlies images on it is parable to the earth which supports the lives in it. The writer then added organic images from linocut prints and geometric images from tire tracks onto the paper, as a representation of human’s action on earth. The organic images visual is referencing organism forms on earth. The theories used to support this final project are art environmental art theory, Gaia 2.0, and land ethics. In the end, the writer’s five final project artworks that are displayed chronologically offer an aesthetic solution for environmental problems, by relaying a statement that earth has the potential to be made into artworks that can be appreciated aesthetically.